Symptoms Versus Problems (SVP) Analysis On Job Dissatisfaction And Managing Employee Turnover: A Case Study In Malaysia - Kader Ali, Noor Nasir; Wilson, Priyah; Yazmin, Ismeth (International Journal of Economics, Commerce and Management United Kingdom, 2015)
Employee turnover and job dissatisfaction are common issues in organizations. The objective of this study is to introduce an improved research method, combining mixed method research with problem identification method (using Symptoms Versus Problems (SVP) framework) for practitioners and to discover the primary causes to the increase in employee turnover rates. MEDICINS, a manufacturer of medical instruments in Malaysia, encounters unfavourable employee turnover rate from 10.88% (2012) to 12.64% (2013). The sequential methodology process, begins with semi-structured interviews, analysis of unpublished company data, customer survey on 214 employees (stratified sampling),followed by field observation are summarized on a root-cause analysis tool structure called Symptoms Versus Problems (SVP) framework. The SVP showed seven major problems, namely, weakness in policies relating to performance management on career growth; lacking in training managers and centers; insufficient training plans to develop leaders; ineffective manpower planning; unclear standard operating procedure (SOP) on training, poor evaluation on production planning and processes; © Noor, Priyah & Ismeth Licensed under Creative Common Page 2 lack in development of effective work culture; and also inter and intra communication issues. These major problems are categorized into three groups, specifically, corporate governance, leadership, planning and execution. The recommendations that addresses corporate governance include review of performance appraisal system; alternative performance appraisal system; and job enrichment. Leadership category focuses on developing good work cultures; communication effectiveness and creating great leaders. Planning &execution category discusses on strategic manpower planning; and SOP training and evaluation. Interestingly, this study discovers another framework on critical success factors for practitioners through development of “House of Pillars for Job Satisfaction and Employee Retention” in Malaysia.